Flavonoid-Rich Extract of Dissotis rotundifolia Whole Plant Protects against Ethanol-Induced Gastric Mucosal Damage - Michael Buenor Adinortey; Charles Ansah; Benjamin Aboagye; Justice Kwabena Sarfo; Orleans Martey; Alexander Kwadwo Nyarko (Biochemistry Research International)
Dissotis rotundifolia is a plant in the family Melastomataceae. The methanolic extract of the whole plant is reported to be rich in C-glycosylflavones such as vitexin and orientin. Though there are several reports on the ethnomedicinal use of this plant extract in stomach ulcers, experimental-based data is unavailable. The drive for carrying out this research was to obtain data on the possible ameliorative effect of the whole plant extract of Dissotis rotundifolia (DRE) in gastric ulcerations induced by ethanol in Sprague Dawley (SD) rats. SD rats were pretreated with 100, 300, and 500 mg/kg of DRE for 14 days after which an ulcerogen-ethanol was administered. Gross examinations of the stomach lining and histological analysis of gastric lesions were carried out coupled with an assessment of the antioxidant activity of gastric mucosa using MDA, GSH, CAT, and SOD as indicators. The data suggested a significant attenuation in gastric mucosal damage in DRE-pretreated ethanol-induced gastric ulcer reflected in the antioxidant status. There was also a reduction or absence of hemorrhage, edema, and leucocytes infiltration in DRE-treated groups compared to the negative control group. DRE conserved glutathione (GSH) levels, reduced malondialdehyde (MDA) levels, and enhanced catalase (CAT) and superoxide dismutase (SOD) enzyme levels. The present study shows that DRE possess protective effects against ethanol-induced ulcer damage in the stomach of rats, which could be attributed to its antioxidant activity.